DESAIN KOMPRESOR MULTI-TAHAP UNTUK OPTIMALISASI PRODUKSI GAS LAPANGAN X - Sari, Dwi Astitie Indah; Sari, Riska Laksmita (Petro : Jurnal Ilmiah Teknik Perminyakan, 2025)
Field X is an old gas field that has experienced a significant decrease in reservoir pressure, thus affecting its production capability. Since 2017, a two-stage compressor system has been implemented to increase gas production which had fallen to 4.5 MMscfd. However, towards the end of 2024, this system is no longer able to maintain flow pressure, so a technical solution is needed. This study aims to evaluate the performance of two-stage compressor systems and design three-stage systems as optimal solutions. Evaluation was carried out using thermodynamic simulations at Aspen HYSYS, well performance analysis using the IPR-VLP approach using PIPESIM, and production forecasting with Decline Curve Analysis (DCA). The results showed that the two-stage system was only able to achieve a discharge  pressure of 354.9 psia, far below the target delivery pressure of 700 psia. The three-stage system is able to achieve a final pressure of 813.7 psia with higher compressor efficiency (80%) and a stable vapour fraction at 1. The IPR-VLP curve shows an increase in production rates of up to 9 MMscfd and DCA projections estimate that the system will be able to withstand the rate of production decline until 2030.